Key concepts in health studies - Yuill, Chris; Crinson, Iain.; Duncan, Eilidh; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2010)
This textbook provides a guide to the central concepts used across health studies, and offers the reader a comprehensive overview of the core topics, theories and debates. It draws together the fundamentals within the disciplines of health nursing, and social policy.
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: Social medicine; Public health; Electronic books